Fueling growth and preventing stunting: the role of animal protein in achieving optimal nutrition - Indonesia's National Nutrition Day 2023 Theme - Dian Novita Chandra (World Nutrition Journal, 2023)
Poor linear growth, currently defined as inadequate height to growth standards defined by the World Health Organization (WHO), is still a major problem in low-middle-income countries (LMICs) including Indonesia. The national survey results from 36.8% in 2007 to 30.8% in 2018 showed small differences in under-five years old children with height-for-age-Z-score less than -2 standard deviation (HAZ < -2 SD) from the growth reference or stunted.1 Though the Indonesian Nutrition Status Survey results showed an improvement in the stunting rate to 21.6% in 2022, the data revealed large regional disparities, ranging from 8% in Bali to 35.3% in East Nusa Tenggara.2 It is known that for children with stunted growth in early life, the risk of impaired health, mortality, and delayed neurocognitive and motor development is heightened. Moreover, tend to have a long-term effect of decreased performance in education, lower productivity and socioeconomics, and a higher risk of chronic diseases in adulthood.1,3 Stunting has many associated factors, including socioeconomic inequality, geographic differences, maternal factors, such as education, age, nutrition status, and infection; short birth intervals, low birth weight, and preterm birth, food insecurity, practices of feeding, nutrient deficiencies, such as protein, iron, zinc, calcium, and vitamins, childhood morbidity, and environmental. Low birth weight and length, unimproved sanitation, and low protein intake are the leading risk factors in developing countries, especially in the horticulture area.4,5